THE IMPLEMENTATION OF LESSON STUDY TO PROMOTE LECTURERS’ SKILL IN TEACHING ACADEMIC WRITING - Lilis Suryani; Ningtyas Orilina Argawati (Universitas Islam Sumatera Utara, 2023)
Lecturers find it challenging to teach writing especially academic writing, since students face difficulties in learning during the study process. This situation may happen because of the inappropriate way of lecturers in covering the material; of all the lecturers should have a good mastery of the materials to be given. Lesson study seems to fit the lecturers' method of practice teaching to improve the skill of teaching writing skills. The study aims to describe the implementation of lesson study by five lecturers to promote the skill of teaching writing. A descriptive qualitative research design was employed with observation and interviews, which were used as the instruments to gather the data. Five lecturers joined the lesson study along with the 45 students in the class. The result shows that using lesson study can promote the lecturers' skill in teaching academic writing by guiding the students in learning, explaining the material of academic writing and varying teaching methods.